"Compromise" Between Human and Nature: A Multi species Ethnography Approach for Redefining the Concept of Human Adaptation - Prihandoko Sanjatmiko; Emil Supriatna (Technium Social Sciences Journal, 2020)
Abstract: In Anthropology, adaptation is interpreted as a variety of human efforts to adapt to the natural environment. This perspective, however, ignores the role of nature as an active subject. In fact, the reciprocal interaction between humans and the nature gives a significant impact to the survival of both entities. This paper intends to recommend a new perspective on the concept of adaptation through the approach of multispecies ethnography. The research observes the people of Kampung Laut in Cilacap. The data is collected through in-depth interviews and participation observations. The paper concludes that the people of Kampung Laut who live around the area where sedimentation takes place always face pressures from the environment as they often encounter tidal flooding. This condition requires the people of Kampung Laut to make efforts in order to survive the unavoidable natural disasters. The people of Kampung Laut "compromise" the environment in Nusakambangan island by growing albizia chinensis plantations. Albizias provide benefits to both the people and the sustainability of the environment. In addition to having a significant economic value, growing albizians among other hardwood trees on the hill of Nusakambangan helps in restoring the environment after the extreme illegal logging. Based on the findings of this research, I argue in accordance to the perspective of multispecies ethnography that the concept of adaptation can no longer place humans as the center of analysis, because this idea tends to disregard the fact that natural disasters are caused by human adaptations. This will ultimately threatens human survival over a period of time.